O sovershenstvovanii psikhologicheskogo obrazovaniya budushchego trenera v sisteme fizicheskoi kul'tury i sporta - Grigoryants, I. A. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
An attempt to conceive, what kind of psychological education must be possessed by future coach at physical culture college was undertaken in this study. Actual status of professional education in the new sports psychology is deeply connected with the modern sports pedagogy. The way to train the prospective coach-educator as a real psycho-analyst is offered in the article. The author considers the principles of new psychological education structure. They will help to modernize the sports psychology course at physical culture higher school. Perfection of psychlogical education in this way will enlarge the professional-psychological sports specialist's preparedness and his perspective social utility. It will make this kind of education to be one of the major factors in the system of higher special education.